BIM-based collaborative design and socio-technical analytics of green buildings - El-Diraby, Tamer; Krijnen, Thomas; Papagelis, Manos (Automation in construction, 2017)
As Building Information Modeling evolves into becoming the central mean for coordinating project design and planning activities, we notice a few limitations/opportunities in the way current BIM tools address the needs for integrated design, collaboration and analysis (the initial objective of BIM). First, substantial communications and interactions about the design exist outside the BIM environment — typically in e-mail formats. This may cause distractions, delays to the project, and could waste valuable knowledge (contained in these interactions). Second, the need of engaging end-users and their keen interest in selecting “green” features. Professionals can develop different designs that achieve varying levels of energy conservation, but these will always require changes based on usage patterns. So, it is important that end-users are involved in the design process early on to make sure that they receive adequate information/ education before they make decisions. This is the nature of limitations that we try to address in this research. This paper builds around the design and development of an online system, named Green2.0 that tries to leverage advancements in Building Information Models (BIM), energy-efficiency simulation tools, and online social network analysis methods to enable a data-driven approach to building planning, construction and maintenance. Fundamentally, it allows participants (end-users or professionals) to comment and share views about building designs. Social network analysis and semantic modeling tools are then used to extract information from these interactions. At the same time, it connects BIM to energy analysis software to allow users to select different products from a catalog and assess the impact of each on energy consumption. The platform aims to advance the current state of the art by bringing about a fundamental shift in the way that AEC professionals, end-users and public policy makers work together throughout a building's lifecycle. Designed as an open platform, it provides access to information that enables researchers and practitioners to build new, more efficient theories and methods of building design. The premise of our work is that by providing new insights into the building design process it is likely to have a profound beneficial effect for both AEC professionals and the society at large. [Display omitted] •Introduced a system for supporting communication & co-commenting within BIM•Created a link between BIM data and social network analysis platforms•Proposed a set of heuristics to transfer BIM data into a format suitable for thermal analysis software